Le développement des droits miniers au Québec à la fin du XIXe siècle - Armstrong, Robert (L'Actualité économique, 1983)
AbstractThis paper examines the forces at work in shaping the definition of mining rights in Quebec at the end of the 19th century. Using the Davis-North model of institutional change and some insights from the theory of rent-seeking, the author attempts to identify the origins of the provincial legal framework which has been in force since the turn of the century.